Effect of Preparation Method and Ni2+ Substitution on the Structural, Thermal, and Optical Properties of Nanocrystalline Lanthanum Zirconate Pyrochlore - Fahad Alharthi; Rizwan Wahab; Salim Manoharadas; Basel F. Alrayes; Naushad Ahmad (Crystals, 2021)
In order to establish the effective application of materials in a particular area, it is important to first investigate the physical and chemical properties, such as the crystallinity, structure, and the optical and surface properties. The objective of the present study is to fabricate thermally stable pyrochlore oxides, namely, lanthanum zirconate (La2Zr2O7, LZ) and Ni-doped lanthanum zirconate (La2Zr1.5Ni0.5O7, LZN) by the solid-state and sol-gel methods. The effects of the preparation and substitution of Zr4+ by Ni2+ for the resulting nanocrystalline samples were characterized in terms of structure, purity, porosity, the thermal and optical properties, and photoluminescence by different techniques: XRD, FT-IR, BET, EDS, TG-DTG, UV-Vis-DRS, and PL. The XRD results confirm that the pyrochlores prepared via the sol-gel method (LZ-sg and LZN-sg) had a cubic unit-cell lattice, whereas the solid-state method (LZ-s and LZN-s) had impurities of the oxides. The XRD patterns, LZ-sg and LZN-sg, were further treated with the Rietveld technique. The textural measurements reveal that LZ-sg had a higher BET surface area compared to LZN-sg. In addition, the substitution of Zr4+ by the Ni2+ ion provides rational evidence for the improvement in the oxygen mobility, as well as the optical and photoluminescence properties through the lowering of the optical band energy and the electron–hole pairs.